Women's involvement in terrorism in Indonesia (A study of nirmilitary defence strategies to counter the threat of terrorism by involving women) - Ratna Damayanti,; Lubis, Amany; Ichsan Malik,; Yusuf Ali,; Agus Adriyanto, (Technium Social Sciences Journal, 2024)
The phenomenon of women's involvement in acts of terrorism around the world is growing, including acts of terrorism in Indonesia that use women as suicide bombers. Terrorism crimes are included in non-military threats so that they must be faced with non- military strategies. In this case, BNPT is the leading sector in implementing non-military strategies to prevent women from being involved in terrorism and also deradicalisation efforts for prisoners, deportees and returnees. The purpose of this study is to analyse how the motives and factors of women can be involved in terrorism and how the non-military defence strategy to overcome women's involvement in terrorism. The research method used is qualitative which is conducted by using desk review technique. The results show that there are two opinions found to be the root cause of women's involvement in terrorism, the first is patriarchy culture and women as victims. But the tendency in Indonesia that occurs is women as victims, the powerlessness of women who are bound by patriarchal culture, the limited insight they have is also the reason so that women are victims of terrorism itself, the findings of the other root of the problem are social inequality or economic problems. Non-military strategy can be implemented by increasing awareness and education for women with a religious approach, economic empowerment, and also women's equality.